PJOK Learning Interest During Covid-19 Pandemic - Hanum, Farida; Alnedral, Alnedral; Aziz, Ishak; Edmizal, Eval; haryanto, jeki; Arifan, Ikhwanul; okilanda, ardo; soniawan, vega (Universitas Negeri Padang, 2022)
The problem in this research is there are students who do not follow and come late in following online learning during this covid-19 pandemic according to the determined schedule. The purpose of this research is to observe how the interest level of PJOK learning of tenth grade students SMA Negeri 7 Padang during covid 19 pandemic. The kind of this research is qualitatif using descriptive method. Population in this research are 435 students. Sampling technique is using random sampling, so the number of sample in this research are 81 students of tenth grade SMA Negeri 7 Padang. The technique of analysis uses persentage. The research result is the student interest in followimg PJOK learning ini SMA negeri 7 Padang during covid 19 pandemic is included in enough category there are 25 students with 30.86% presentage, in high category are 52 students witj 64.20% presentage, ini very high category are 4 students with 4.94% percentage. Overall, the clasification of PJOK learning level is included in high catogory with respondent achievement level is 64.20% .